Hepatitis B virus infection correlates with poor prognosis of extranodal natural killer/T cell lymphoma. Issue 4 (April 2015) - Wang, Liang; Wu-Xiao, Zhi-jun; Chen, Xiao-qin; Zhang, Yu-jing; Lu, Yue; Xia, Zhong-jun
Abstract Studies have shown that hepatitis B virus (HBV) infection may play an important role in the lymphomagenesis of lymphoma, but no studies regarding the relationship between HBV infection and extranodal natural killer/T cell lymphoma (ENKTL) have been reported previously. One hundred and seven patients diagnosed with ENKTL were retrospectively reviewed. The hepatitis B surface antigen (HBsAg)-positive rate was 13.1%, and no significant correlation existed between HBV infection and clinical characteristics (p > 0.05). No significant difference existed in complete remission rate between HBsAg-positive and -negative groups (42.9% vs. 44.1%, p = 1.000). In a multivariate Cox regression model that included international prognostic index (IPI) score, induction chemotherapy regimen and HBsAg status, all these variables were independent prognostic factors for overall survival (OS) and progression-free survival (PFS) (p < 0.05). In conclusion, the HBsAg-positive rate in ENKTL was similar to that of the normal population in a high HBV endemic area, and HBsAg-positive status was an independent prognostic factor for OS and PFS.